1998
DOI: 10.1046/j.1523-5378.1998.08002.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Rapid Whole Blood Test for Helicobacter pylori in Primary Care: A German Multicenter Study

Abstract: We found the performance of the BM test to be insufficiently accurate, as both over- and underdiagnosis of H. pylori infection were not infrequent. This test needs to be improved before its use in primary care can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
1
9
0
2
Order By: Relevance
“…Assessments of other microbiology near patient tests (streptococcal throat tests,2225 Helicobacter pylori ,2628 and Plasmodium falciparum antigens29) were severely hampered by a lack of agreement on the standard for evaluation. For example, the three H pylori studies used the same test (Helisal Rapid Blood, Cortecs) but different reference standards.…”
Section: Resultsmentioning
confidence: 99%
“…Assessments of other microbiology near patient tests (streptococcal throat tests,2225 Helicobacter pylori ,2628 and Plasmodium falciparum antigens29) were severely hampered by a lack of agreement on the standard for evaluation. For example, the three H pylori studies used the same test (Helisal Rapid Blood, Cortecs) but different reference standards.…”
Section: Resultsmentioning
confidence: 99%
“…However, histological observation and the rapid urease test require endoscopy, UBT is very expensive, and serological tests require blood drawing. Recently, a rapid test using whole blood has been developed as a rapid method [15], but it has been also reported that the accuracy of the results was unreliable [16].…”
Section: Discussionmentioning
confidence: 99%
“…Currently antibody detection in urine or saliva [99] are not sufficiently validated as tests for an immune response to H. pylori. This is also the case for quick tests for the antibody detection in whole blood [100,101]. Test kits to detect H. pylori-IgG-antibodies in serum should be validated for their use in Europe.…”
Section: Guideline Validity !mentioning
confidence: 99%